A163 MICROCOSTING: ASSESSING HEALTH ECONOMICS IN GI. (26th February 2020) - Gillies, A N; Chow, R; Galorport, C; Telford, J J; Enns, R A
Abstract: Background: Micro-costing is a method of collecting precise cost measurements and proves effective in determining economic requirements needed to support health interventions. At St. Paul's GI Clinic, over 12000 procedures are performed yearly, 80% of which are colonoscopies. Specific standards in the form of appropriate documentation are recommended through Global Rating Scale (GRS) and require yearly auditing to ensure appropriate compliance with these standards. These audits require a time commitment of staff to assess charts. The cost of performing these assessments is not known. Aims: To determine the cost of annual data collection suggested by GRS for documentation of procedures. Methods: A retrospective chart review and data analysis of patients (≥ 19 years old) admitted to St. Paul's GI Clinic for a colonoscopy and/or esophagogastroduodenoscopy (EGD). Data is extracted from the St. Paul's medical database from August 1 st 2018 – August 1 st 2019. Since it is a 'time-and-motion' study, a stopwatch is used to time the collection of data from each chart. The mean time per-case is derived and used to conduct an appropriate economic analysis, such as total working hours, per-minute salary calculations and equipment costs. The purpose is to determine a yearly cost and identify what the main cost drivers were (time/labor). Results: As per our annual review format suggested by GRS, 260 procedure reports were reviewed, 150 colonoscopies and 110 EGDs (random sampling of 10 per physician for each type of procedure). A spread sheet outlining key data assessment points for mandatory standard reporting points has been used yearly and was used for this study as well. Mean evaluation time (including recording presence or absence of each item on our standard reporting form): 1 minute and 40 seconds to review the report for a colonoscopy and 1 minute and 33 seconds to review the report for an EGD. A total of 2 hours 51 minutes 16 seconds to review all the EGD reports and 4 hours 8 minutes and 46 seconds for the colonoscopy reports. Conclusions: It would cost $126 annually to pay a research student, who makes $18/ hour, to collect this quality assurance data required for auditing completeness of physician colonoscopy and EGD procedure documentation according to standards. Funding Agencies: None